2 (3) 4 = 14 and 3 (4) 6 = 60 and then 4 (5) 7=
Answers
Answer: 96
Step-by-step explanation:
2 [3] 4 = 14 can be obtained from
⇒[ (4+3) * 2 ] * [4 - 3]
⇒[ 7 * 2 ] * 1
⇒14
Similarly, 3 [4] 6 =60 can be obtained from
⇒[ ( 6 + 4 ) * 3 ] * [ 6 - 4 ]
⇒[ 10 * 3 ] * [2]
⇒ 60
Hence we analyzed that if :
a [b] c is given it's answer can be obtained by solving
⇒ [ ( c + b) * a ] * [ c - b ]
So, the answer of 4 [5] 7 is:
⇒[ (7 + 5) * 4 ] * [ 7 - 5 ]
⇒[12 * 4] * 2
⇒ 48 * 2
⇒ 96
The value of 4 (5) 7 = 96.
Step-by-step explanation:
We have,
2 (3) 4 = 14 and 3 (4) 6 = 60
To find, the value of 4 (5) 7 = ?
The pattern follow:
[(Third term + Second term) × First term] × (Third term - Second term) .
2 (3) 4 = [(4 + 3) × 2] × (4 - 3) = [7 × 2] × 1 = 14 × 1 = 14
3 (4) 6 = [(6 + 4) × 3] × (6 - 4) = [10 × 3] × 2 = 30 × 2 = 60
Similarly,
? = 4 (5) 7 = [(7 + 5) × 4] × (7 - 5) = [12 × 4] × 2 = 48 × 2 = 96
∴ Missing number = 96
Hence, the value of 4 (5) 7 = 96.